Comparison between various densities of pore titanium meshes and e-polytetrafluoroethylene (ePTFE) membrane regarding bone regeneration induced by low intensity pulsed ultrasound (LIPUS) in rabbit nasal bone. Issue 9 (September 2016) - Higuchi, Masatoshi; Moroi, Akinori; Yoshizawa, Kunio; Kosaka, Akihiko; Ikawa, Hiroumi; Iguchi, Ran; Saida, Yuriko; Hotta, Asami; Tsutsui, Takamitsu; Ueki, Koichiro
Abstract: Purpose: The purpose of this study was to compare bone regenerative capability following use of polytetrafluoroethylene (ePTFE) membrane against that when various densities of pore titanium meshes are used with and without low intensity pulsed ultrasound (LIPUS). Materials and methods: Adult male white rabbits were divided into 8 groups. In 4 groups, after incising along the nasal bone, four 3 × 8 mm bone defects were made in both sides and covered by an ePTFE membrane (group E: n = 15), a high density pore titanium mesh (group H: n = 15), a low density pore titanium mesh (group L: n = 15), and no mesh (control) (group C: n = 15). Furthermore, LIPUS was irradiated after surgery in 4 groups (groups EL, HL, LL and CL, in each n = 15). The rabbits were sacrificed at 1, 2 and 8 weeks postoperative, and formalin-fixed specimens were embedded in acrylic resin. The specimens were stained with hematoxylin and eosin. For immunohistochemical analysis, the specimens were treated with bone morphogenetic protein (BMP)-2 antibody. Results: Group H had significantly higher values than groups L, E, and C regarding bone area ratio and labeling index of BMP-2 positive cells (P < 0.05). Furthermore, Group HL also had significantly higher values than the other groups regarding bone area ratio and labeling index of BMP-2 positive cells at 1, 2 and 8 weeks postoperative (P < 0.05). Conclusion: The results suggested that high density pore titanium mesh could induce new bone regeneration more than low density pore titanium mesh and ePTFE membrane. New bone formation may increase following LIPUS application.